Client Ratings of a University Counselling Service and Respondent Anonymity - Miller, Gary H. (Canadian Journal of Counselling and Psychotherapy, 2012)
Clients of a university counselling service who responded to a mailed follow-up questionnaire were classified as anonymous respondents if they removed an identifying number from the questionnaire. Large and significant differences between identified and anonymous respondents were reported with anonymous respondents reporting fewer positive changes for the time period between initial and final contact with the counselling service. The implications of these results for follow-up studies are discussed.